We Get Nothing from Fishing. Fishing for Boat Opportunities Amongst Senegalese Fisher Migrants. (Langaa RPCIG, 2010)
The world is regularly confronted on television and in other mass media with dramatic images of African boat migrants. Seemingly desperate, these Africans, most of them males, are willing to risk a perilous journey at sea, hoping for a better life in Europe. And, even worse, hundreds more are believed to die each year, swallowed up anonymously by the choppy waters off Africa's coast. This book focuses on fishermen who have played a pivotal role in boat migration from Senegal to Spain's Canary Islands, advancing various reasons for the fishermen's prominent role. Besides their long history of migration, their proven experience with navigating, their family's push and investment, their perceptions and ideologies about Europe, there is also their growing marginalization as a result of the deepening crisis in the Senegalese fishing sector and the inadequate policies of the Senegalese government that prevents them from having any bright prospects of improving their standards of living. The book provides deep insights into the meaning of boat migration, and on the effects of success or failure on the migrants and their families. It goes beyond the usual economic explanations to convincingly situate boat migration within the long-standing West African culture of migration, and highlight the significance of socio-cultural and political factors. Among the fascinating findings are the perception of migration as status enhancing and a rite de passage in the Senegalese fishing communities, and the profound roles of the extended family, social networks and, above all, religion, especially the widespread influence of the marabout. The importance of information and communication technologies in sustaining transnational networks is equally highlighted.